Teachers’ pedagogical competence in teaching 21st-century skills of global and local connectedness - Getahun, Amsalu Molla (Universitas Negeri Semarang, 2025)
This study employed a mixed-embedded research design, collecting data from teachers (n = 188) via a questionnaire and conducting in-depth interviews with ten participants. The primary aim was to analyse pedagogical competence in teaching 21st-century skills related to global and local connectedness at Tewodros II Secondary School in Ethiopia. The results indicated that teachers' competencies in fostering global and local connectedness were unsatisfactory, leading to challenges in cultivating these dimensions among students. The findings highlight the urgent need for targeted interventions in teaching global and local connectedness as part of 21st-century skills. Such efforts are essential to developing citizens equipped to navigate global and local challenges within the school environment and the wider society. Therefore, this research contributes significantly to bridging the global and local education issues.